2016
DOI: 10.1155/2016/4012912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quorum Sensing Systems on Regulatory T Cells in Catheter-RelatedPseudomonas aeruginosaBiofilm Infection Rat Models

Abstract: Background. Quorum sensing (QS) systems play an important role in modulating biofilm formation. Recent studies have found that the QS molecules had complex effects on the host immune systems. In addition, regulatory T cells (Tregs), known as important negative regulators in the immune system, have been found upregulated in multiple chronic infections. Therefore, the QS systems were hypothesized to be involved in modulating Tregs in biofilm-associated infections. Object. To explore the effects of QS systems on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Although they play a critical role in promoting bacterial growth and survival, they can cause devastating injuries to the host tissues and impair the immune responses. QS deficient mutants cause considerably less tissue damage and pathological changes during infections due to a significant decrease in the virulence and cytotoxicity (Nelson et al, 2009 ; Feng et al, 2016 ).…”
Section: Central Regulatory Role Of Quorum Sensing (Qs) For Virulencementioning
confidence: 99%
“…Although they play a critical role in promoting bacterial growth and survival, they can cause devastating injuries to the host tissues and impair the immune responses. QS deficient mutants cause considerably less tissue damage and pathological changes during infections due to a significant decrease in the virulence and cytotoxicity (Nelson et al, 2009 ; Feng et al, 2016 ).…”
Section: Central Regulatory Role Of Quorum Sensing (Qs) For Virulencementioning
confidence: 99%
“…P. aeruginosa pigment molecules, pyocyanin and 1-hydroxyphenazine, in association with the tryptophan catabolic product kynurenine, produced by both the bacterium and host, appear sufficient to activate AHR during infection (78,79,163). In a rat catheterrelated lung infection model examining P. aeruginosa QS mutants, the production of suppressive cytokines (IL-10, TGF-b) and the presence of T regulatory lymphocytes were higher in the animals infected with the wild-type bacteria than in animals challenged with the mutants (164), suggesting that QS molecules also affect the induction of certain T-cell subsets.…”
Section: T Cells and Baltmentioning
confidence: 99%
“…In patients with cystic fibrosis, the growth of bacteria in biofilm determines aggravation of the disease. Recent studies have found that the QS molecules interact with eukaryotic cells and modulate also host immune response [ 9 ]. But, although the roles of the N -acylhomoserine lactones in the modulation of immune response have been well studied, the results obtained until now were contradictory, depending on the cell line, the concentration and the time of action [ 10 ].…”
Section: Introductionmentioning
confidence: 99%